Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

staceyyyy1

  • 3 years ago

[2.03] Solve: 4(2x − 1) − 3 = 9(x − 4) −29 <--- ? 32 13 29

  • This Question is Closed
  1. ParthKohli
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Let me try

  2. ParthKohli
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    \( \color{Black}{\Rightarrow 8x - 4 - 3 = 9x - 36 }\) \( \color{Black}{\Rightarrow 8x - 7 = 9x - 36 }\) \( \color{Black}{\Rightarrow 8x = 9x - 29 }\) \( \color{Black}{\Rightarrow -x = -29 }\)

  3. ParthKohli
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Oopsie....you got a sign wrong

  4. ParthKohli
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    \( \color{Black}{\Rightarrow -a = -b \Longleftrightarrow a = b }\)

  5. ParthKohli
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    \( \color{Black}{\Rightarrow -x = -29 \Longrightarrow x = 29 }\)

  6. staceyyyy1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thanks Again!(:

  7. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy